Depression, Suicidal Behaviour, and Mental Disorders in Older Aboriginal Australians - Shen, Yu-Tang (Int J Environ Res Public Health, 2018)
Aboriginal Australians experience higher levels of psychological distress, which may develop from the long-term sequelae of social determinants and adversities in early and mid-life. There is little evidence available on the impact of these on the mental health of older Aboriginal Australians. This study enrolled 336 Aboriginal Australian participants over 60 years from 5 major urban and regional areas in NSW, utilizing a structured interview on social determinants, and life-time history of physical and mental conditions; current psychosocial determinants and mental health. Univariate and multivariate analyses were utilized to examine the link between these determinants and current depressive scores and suicidality. There was a high rate of life-time depression (33.3%), current late-life depression (18.1%), and suicidal ideation (11.1%). Risk factors strongly associated with late-life depression included sleep disturbances, a history of suicidal behaviour, suicidal ideation in late-life and living in a regional location. This study supports certain historical and psychosocial factors predicting later depression in old age, and highlights areas to target for prevention strategies.